Extending the expectation confirmation model toward sustainable relationship continuance: the mediating roles of engagement and financial empowerment in Indonesian mobile banking - Neviana,; Warganegara, Dezie Leonarda (Frontiers in Sustainability, 2026)
This study extends the expectation–confirmation model for information systems (ECM-IS) toward a sustainability-oriented account of post-adoption behavior by explaining how engagement and financial empowerment sustain long-term digital relationships. Motivated by the gap between widespread mobile banking adoption and fragile post-adoption use in emerging markets, the study uses mobile banking in Indonesia as the empirical context. We specify engagement and financial empowerment as parallel mediating mechanisms linking experience quality, perceived personalization, and trust to sustainable relationship continuance. Survey data from 306 mobile banking users were analyzed using partial least squares structural equation modeling (PLS-SEM) with validated measurement scales and bootstrapped mediation tests. The results show that engagement and financial empowerment jointly support sustainable relationship continuance. Perceived personalization is the strongest driver of engagement, while trust and experience quality primarily build financial empowerment, with personalization also contributing to capability formation. Conceptually, the study advances post-adoption theory by demonstrating that capability-based empowerment represents a pathway that is distinct from yet complementary to relational connection, thereby extending ECM-IS beyond single-path continuance explanations toward sustainable relationship continuance. Practically, the findings suggest that organizations can orchestrate responsible personalization, transparent consumer protection, and reliable service quality to strengthen trust, deepen connection, and enhance user capability. Overall, the proposed mediating framework links post-adoption behavior to sustainability by showing how connection and capability convert experience quality, personalization, and trust into durable commitment in a regulated emerging market.